Engineering ARMMs for improved intracellular delivery of CRISPR-Cas9 - Zunwei Chen; Qiyu Wang; Quan Lu (Extracellular Vesicle)
CRISPR-Cas9-based gene editing holds enormous promise for therapeutic applications, but its effectiveness is often limited by inefficient delivery methods. This study explores the potential of arrestin domain-containing protein 1 (ARRDC1)-mediated microvesicles (ARMMs)—a type of extracellular vesicles formed at the plasma membrane—as a novel platform for packaging and delivering CRISPR-Cas9 complexes. We achieved efficient Cas9 packaging into ARMMs by directly fusing Cas9 with ARRDC1. Two different ARRDC1-Cas9 fusion constructs were designed, and both demonstrated gene-editing efficiency comparable to unmodified Cas9. The fusion with a shorter version of ARRDC1 (sARRDC1), which includes only the minimal motifs required for vesicle budding, proved particularly effective in enhancing Cas9 packaging. Additionally, the incorporation of vesicular stomatitis virus glycoprotein (VSV-G) further improved ARMMs budding and Cas9 encapsulation. We tested gene editing in U2OS cells with an exogenous GFP gene and in human neuronal cells targeting the endogenous amyloid precursor protein (APP) gene, which is associated with the Alzheimer's disease. The combination of ARMMs and VSV-G resulted in high editing efficiency, with ARMMs targeting the APP gene in neuronal cells significantly reducing pathogenic amyloid peptides. These results highlight ARMMs as a versatile and effective platform for CRISPR-Cas9 delivery, with strong potential for therapeutic applications in neurodegenerative and other genetic diseases.